Pengembangan Media Pembelajaran Interaktif Berbasis Lectora Inspire Pada Materi Norma dan Keadilan Pada Mata Pelajaran PPKn di Kelas VII B SMPN 30 Muaro Jambi - Sri Devi, Agustina; Sutja, Akmal; Usmanto, Heri (Civic Education Perspective Journal, 2022)
This research was motivated by the problems at SMPN 30 Muaro Jambi, especially the low learning outcomes of class VII B students which only reached 32% of students who reached the KKM. In addition, teachers face challenges in producing learning materials that will excite students' interest as they learn, enabling them to improve student learning outcomes. This study aims to create an interactive learning media based on Lectora that inspires material on norms and justice to help grade VII B students of SMPN 30 Muaro Jambi improve Civics learning outcomes. The ADDIE development model is of this type (Analysis, Design Development, Implementation, and Evaluation). This research makes interactive learning media by giving assessments to students to find out their learning outcomes. An assessment questionnaire filled out by a team of experts, teachers, and students was used in this study. Based on research on student learning outcomes tests at the end of the learning activity, there were 26 students who obtained complete scores and two students with incomplete scores from a total of 28 students whose learning outcomes increased by 93%.